2021
DOI: 10.1101/2021.01.07.425786
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An endosome-associated actin network involved in directed apical plasma membrane growth

Abstract: The actin cytoskeleton participates in a range of cellular processes. It supports cell shape changes by propagating forces within cells and between cells and their environment. Terminal cells of the Drosophila respiratory system form a subcellular tube by invaginating their apical plasma membrane; cortical actin networks at the basal and apical plasma membranes are critical for proper morphogenesis. Basal actin affects apical membrane morphogenesis, and it is not known how the two separate actin pools communic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Therefore, disrupting MTs by expression of the MT-severing protein Spastin uncouples directed growth of the apical compartment and results in guidance defects ( Gervais and Casanova, 2010 ). Disrupting actin organisation in any subcellular compartment also prevents coordinated apicobasal growth ( Gervais and Casanova, 2010 ; JayaNandanan et al, 2014 ; Levi et al, 2006 ; Okenve-Ramos and Llimargas, 2014 ; Ríos-Barrera and Leptin, 2021 preprint).…”
Section: Apicobasal Growth Coordination During Subcellular Tube Formationmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, disrupting MTs by expression of the MT-severing protein Spastin uncouples directed growth of the apical compartment and results in guidance defects ( Gervais and Casanova, 2010 ). Disrupting actin organisation in any subcellular compartment also prevents coordinated apicobasal growth ( Gervais and Casanova, 2010 ; JayaNandanan et al, 2014 ; Levi et al, 2006 ; Okenve-Ramos and Llimargas, 2014 ; Ríos-Barrera and Leptin, 2021 preprint).…”
Section: Apicobasal Growth Coordination During Subcellular Tube Formationmentioning
confidence: 99%
“…Another actin-based structure involved in subcellular tube formation lies in the space between the tip of the subcellular tube and the cell-growth cone, and it is referred to as the actin core ( Gervais and Casanova, 2010 ; Okenve-Ramos and Llimargas, 2014 ; Oshima et al, 2006 ). We recently showed that late endosomes are responsible for the formation of this structure by promoting actin nucleation through Wash, a Wiscott-Aldrich Syndrome Protein (WASP) member ( MacDonald et al, 2018 ; Mathew et al, 2020 ; Nagel et al, 2017 ; Ríos-Barrera and Leptin, 2021 preprint). Late endosomes and the associated actin core precede subcellular tube growth and branching, and inducing their mislocalisation affects directed apical membrane growth.…”
Section: Apicobasal Growth Coordination During Subcellular Tube Formationmentioning
confidence: 99%
See 3 more Smart Citations